SOME ISSUES OF CONDUCTING AN INVESTIGATIVE EXPERIMENT (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article considers a number of tactical conditions that must be met in the preparation and conduct of an investigative experiment, as well as tactical methods that can be used by the investigator in the implementation of this procedural action. At the same time, the general tactical conditions for conducting an investigative experiment, as well as any investigative action in general, must meet certain general requirements: it must be legal, ensure the objectivity of the research and achieve the set goal. The legality of the tactical method is determined by how well they correspond to the applicable legal norms and principles.